Efficacy, Immunogenicity and Safety of Vaccination in Pediatric Patients With Autoimmune Inflammatory Rheumatic Diseases (pedAIIRD): A Systematic Literature Review for the 2021 Update of the EULAR/PRES Recommendations - Jansen, Marc H.; Rondaan, Christien; Legger, Geertje; Minden, Kirsten; Uziel, Yosef; Toplak, Nataša; Maritsi, Despoina; van den Berg, Mirjam; Berbers, Guy; Bruijning, Patricia; Egert, Yona; Normand, Christophe; et al. (Frontiers in Pediatrics, 2022)
Background In 2011, the first European League Against Rheumatism (EULAR) vaccination recommendations for paediatric patients with autoimmune inflammatory rheumatic diseases (pedAIIRD) were published. The past decade numerous new studies were performed to assess the safety, efficacy and immunogenicity of vaccinations in pedAIIRD. A systematic literature review (SLR) was therefore performed to serve as the basis for the updated 2021 EULAR/PRES recommendations. Methods An SLR was performed according to the standard operating procedures for EULAR-endorsed recommendations. Primary outcomes were efficacy, immunogenicity and safety of vaccination in pedAIIRD. The search was performed in Medline, Embase and the Cochrane Library and included studies published from November 2010 until July 2020. Results: The SLR yielded 57 studies which were included for critical appraisal and data extraction. Only 8 studies described the occurrence of vaccine-preventable infections after vaccination (efficacy), none of these studies were powered to assess efficacy. The majority of studies assessed (humoral) immune responses as surrogate endpoint for vaccine efficacy. Studies on non-live vaccines showed that these were safe and in general immunogenic. Biologic disease-modifying antirheumatic drugs (bDMARDs) in general did not significantly reduce seroprotection rates, except for B-cell depleting therapies which severely hampered humoral responses. Four new studies on human papilloma virus vaccination showed that this vaccine was safe and immunogenic in pedAIIRD. Regarding live-attenuated vaccinations, level 1 evidence of the measles mumps rubella (MMR) booster vaccination became available which showed the safety of this booster for patients treated with methotrexate. In addition, level 3 evidence became available that suggested that the MMR and varicella zoster virus (VZV) vaccination for patients on low dose glucocorticosteroids and bDMARDs might be safe as well. Conclusions: The past decade, knowledge on the safety and immunogenicity of (live-attenuated) vaccines in pedAIIRD significantly increased. Data on efficacy (infection prevention) remains scarce. The results from this SLR are the basis for the updated EULAR/PRES vaccination recommendations in pedAIIRD.